Proceedings of the International Water Association Conference & Exhibition on Water & Wastewater Management for Developing Countries, Kuala lumpur, 29-31 Oktober 2001 - The International Water Association Conference & Exhibition on Water & Wastewater Management for Developing Countries (2001 : Kuala Lumpur); International Water Association; Universiti Teknologi Malaysia (Skudai : Institute of Environmental & Water Resource Management, Universiti Teknologi Malaysia, 2001)
10